Work Period as one of The Risk Factors of Suspected Carpal Tunnel Syndrome (CTS) among Worker in the “X” Furniture Manufacturing, Gresik-East Java 2018 - Dyandarasmi Larasati; Sulistiawati; Andre Triadi Desnantyo (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Carpal Tunnel Syndrome (CTS) is a nerve disorder where an entrapped median nerve in the carpal tunnel causes pain and numbness in the hand. Prolonged condition of CTS will decrease someone’s productivity in daily life that requires hand. Aim: This study aimed to analyze age, sex, and work period as the risk factors that can increase the incidence of suspected CTS in workers at the